2020
DOI: 10.1007/s42000-020-00179-w
|View full text |Cite
|
Sign up to set email alerts
|

Environment-wide association study to comprehensively test and validate associations between nutrition and lifestyle factors and testosterone deficiency: NHANES 1988–1994 and 1999–2004

Abstract: Purpose-Testosterone (T) plays an important role in men's health and its deficiency is linked with poorer health. Yet, the role of nutritional and lifestyle factors in T regulation and production remains unclear. The objectives are to comprehensively test the cross-sectional associations of nutritional and lifestyle factors with T deficiency and to validate the associations in the NHANES survey. Methods-We performed weighted multivariable logistic regression analysis to examine the association of 173 nutrition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The EWAS was proposed to identify multiple environmental factors (173 to 266 nutritional and lifestyle factors) associated with complex diseases (e.g. deficiency testosterone 67 , peripheral arterial disease 68 ) by borrowing the GWAS methodology, including a data-driven analysis. To our knowledge, the present study was the first to examine the 3D facial morphology based on multiple environmental factors (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The EWAS was proposed to identify multiple environmental factors (173 to 266 nutritional and lifestyle factors) associated with complex diseases (e.g. deficiency testosterone 67 , peripheral arterial disease 68 ) by borrowing the GWAS methodology, including a data-driven analysis. To our knowledge, the present study was the first to examine the 3D facial morphology based on multiple environmental factors (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…31 Frequently-studied health outcomes were type 2 diabetes, 30,32,33 obesity, 34,35 and blood pressure. 36,37 Other outcomes included liver enzymes, 38 mental and social well-being, 39 testosterone deficiency, 40 diabetic retinopathy, 41 multiple sclerosis, 42 peripheral arterial disease, 43 and cardiovascular disease. 44 However, no studies have simultaneously and comprehensively examined environmental chemical exposures associated with cognitive decline in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…A negative correlation between serum phosphorus and testosterone (T) level was also found in older men [16]. In addition, dietary phosphate intake is inversely associated with T de ciency in humans [17] and with IR in mice [18]. However, to the best of our knowledge, only one previous study reported a negative correlation relationship between serum phosphorus and IR in women with PCOS, and most of these patients were obese [19].…”
Section: Introductionmentioning
confidence: 99%